Effect of Pre-Harvest Foliar Application of Citric Acid and Malic Acid on Chlorophyll Content and Post-Harvest Vase Life of Lilium cv. Brunello - Darandeh, Nafiseh; Hadavi, Ebrahim (Frontiers in Plant Science, 2012)
Citric acid is a regular ingredient in many vase solution formulations but pre-harvest use of citric acid is a novel method in vase life extension of cut flowers, which is reported on tuberose earlier. In order to verify previous result, and check for possible substitution of citric acid by malic acid, the current research was designed. Citric acid (0, 0.075, 0.15% w/v) and malic acid (0, 0.075, 0.15% w/v) were used in a factorial design with three replications. Foliar sprays were applied two times during growth period of Lilium plants. The results point out that 0.15% citric acid alone had increased vase life from 11.8 in control treatment to 14 days (α < 0.05). The interesting finding was the effect of citric acid on bulbil weight, which was decreased from 9 g in control to 1.5 g in treatment containing combination of 0.075% citric acid and 0.075% malic acid. Malic acid while having no direct effect on pre-mentioned traits surprisingly increased the chlorophyll content significantly. The interaction effect between citric acid and malic acid on vase life and chlorophyll content proved significant and was evident in results, both as antagonistic and synergistic in various traits.